INNOVATIONS ACTIVENESS IN THE SMES SECTOR IN BULGARIA AND SPAIN: EMPIRICAL STUDY - Lina Anastassova; Atanas Luizov; Esther Subira; Carlos Grau (World Science, 2018)
Innovations are one of the most influential factors on the economic growth and this is the reason why governments nowadays have significant concern about it. Researchers and academics from many countries study the innovations activeness and the type of innovations in various industry sectors but comparing the big scope of academic research on international level, there is insufficient research on the topic of innovativeness in Bulgaria. And as SMEs present a significant part of the regional and national economies including in Bulgaria, this empirical survey in Bulgaria and Spain is based on samples of SMEs from different sectors in both countries. In order to guarantee comparativeness the same questioning instrument was employed and the analysis revealed many similarities in the attitude to innovations and the type of innovations in small and medium sized companies in both countries. According to the survey results, the SMEs in Bulgaria focus more on innovations in the promotional policy egg. the marketing communications in contrast with the small and medium-sized companies in Spain where the stress in innovations is more on changes in distribution channels and in the pricing strategies. The comparative analysis with the Spanish companies points out that concerning the innovations in “design and packaging of goods” and “usage of new methods for goods and services promotion” the behaviour of the Bulgarian and Spanish companies is similar. At the end of the paper are drawn some conclusions about the innovations activeness of the SMEs in both countries and the similar problems.